STARTUP FINANCING: MODERN APPROACHES AND OPPORTUNITIES FOR ENTREPRENEURS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
: Startup financing is one of the most important factors influencing the success and sustainability of new business ventures. Access to financial resources enables entrepreneurs to develop innovative products, enter markets, expand operations, and compete effectively in the modern economy. However, obtaining sufficient funding remains a major challenge for many startups, particularly during the early stages of development. This article examines the concept of startup financing, its significance for entrepreneurial activity, and the main sources of funding available to startup founders. Special attention is given to self-financing, bank loans, venture capital, angel investors, crowdfunding, and government support programs. The study highlights the importance of selecting appropriate financing strategies to ensure business growth and long-term success.
Keywords: startup, startup financing, entrepreneurship, venture capital, angel investors, crowdfunding, business development, investment, innovation.